Effects of temperature on lung and blood gases in the South American rattlesnake Crotalus durissus terrificus - Wang, T.; Abe, Augusto Shinya [UNESP]; Glass, M. L. (Elsevier B.V., 1998)
The effects of temperature on lung and blood gases were measured in the South American rattlesnake (Crotalus durissus terrificus). Arterial blood and lung gas samples were obtained from chronically cannulated animals at 15, 25, and 35 degrees C. As expected for reptiles, arterial pH fell with increased temperature (0.018 U degrees C-1 between 15 and 25 degrees C and 0.011 U degrees C-1 between 25 and 35 degrees C) while lung gas PCO2 rose from 5.8 mmHg at 15 degrees C to 13.2 mmHg at 35 degrees C. Concurrently, lung gas PO2 declined from 132 mmHg at 15 degrees C to 120 mmHg at 35 degrees C, and arterial PO2 increased from 33 to 76 mmHg in that temperature range. Arterial haemoglobin O-2 saturation rose from 0.53 at 15 degrees C to 0.83 at 25 degrees C but became slightly reduced (0.77) with a further elevation of temperature to 35 degrees C. Arterial haemoglobin concentration increased from 1.96 to 2.53 mM between 15 and 35 degrees C, consistent with higher demands on oxygen delivery to tissues at elevated temperatures. Moreover, the substantial increase of haemoglobin O-2 saturation between 15 and 25 degrees C conforms to the idea that reduction of the central vascular right-to-left shunt (pulmonary bypass of systemic venous return) is associated with high metabolic demands. (C) 1998 Elsevier B.V. All rights reserved.
Keywords: reptile; snake; Crotalus; temperature; acid-base balance; O-2 transport; lung gases; arterial blood gases